Conclusions and perspectives - 480081 Proceedings of the world conference sponsored by Institut de la Vie and held in Paris, Sept 9-13, 1974; Marois, Maurice; Proceedings of the world conference (1974: Paris) (Oxford : Pergamon Press, 1977)
01